Solutions of some nonlinear equations by a direct algebraic method - İnan, İbrahim E.; Uğurlu, Yavuz; Duran, Serbay (My University, 2011)
In this paper, we present a direct algebraic method which is suggested by H. Zhang for the exact solutions of the Benjamin-Bona-Mahony (BBM), (3+1) dimensional Kadomtsev—Petviashvili (KP) and Caudrey-Dodd- Gibbon Kawada (CDGK) equation.
Keywords: Matematik